Nanostructured chitosan/maghemite composites thin film for potential optical detection of mercury ion by surface plasmon resonance investigation - Muhamad Fauzi, Nurul Illya; Yap, Wing Fen; Sheh Omar, Nur Alia; Saleviter, Silvan; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Hashim, Hazwani Suhaila; Mohd Nasrullah (Multidisciplinary Digital Publishing Institute, 2020)
In this study, synthesis and characterization of chitosan/maghemite (Cs/Fe2O3) composites thin film has been described. Its properties were characterized using Fourier transform infrared spectroscopy (FTIR), atomic force microscopy (AFM) and ultraviolet-visible spectroscopy (UV-Vis). FTIR confirmed the existence of Fe–O bond, C–N bond, C–C bond, C–O bond, O=C=O bond and O–H bond in Cs/Fe2O3 thin film. The surface morphology of the thin film indicated the relatively smooth and homogenous thin film, and also confirmed the interaction of Fe2O3 with the chitosan. Next, the UV-Vis result showed high absorbance value with an optical band gap of 4.013 eV. The incorporation of this Cs/Fe2O3 thin film with an optical-based method, i.e., surface plasmon resonance spectroscopy showed positive response where mercury ion (Hg2+) can be detected down to 0.01 ppm (49.9 nM). These results validate the potential of Cs/Fe2O3 thin film for optical sensing applications in Hg2+ detection.